2000
DOI: 10.1002/1097-4628(20001107)78:6<1304::aid-app160>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of solute organic compounds and water in poly(dimethylsiloxane)

Abstract: The properties of an aqueous solution are interesting depending on its application. Their characteristics are mainly a result of a hydrophobic interaction. The permeation behavior, particularly for an aqueous solution with a hydrophilic solute, is affected by the hydration of water to the solute. In case of an aqueous solution of organic compounds, generally, the water molecule adjacent to the solute become less mobile than in the pure water due to hydration. The hydration may affect the diffusivity of solute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Membrane techniques for the removal of VOCs in water can offer potential savings in energy costs. Many studies have been reported on the permeation and removal of VOCs from water by various hydrophobic polymer membranes, mainly composed of poly(dimethylsiloxane) (PDMS), [18][19][20][21][22][23][24][25][26][27][28] zeolite-filled PDMS, [29,30] and various other materials. [31][32][33] In this study, for the purpose of removal of VOCs, such as benzene, from water we prepared organic-inorganic hybrid membranes by the sol-gel method using alkyl methacrylate as an organic compound having high affinity for VOCs and TEOS as an inorganic compound.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane techniques for the removal of VOCs in water can offer potential savings in energy costs. Many studies have been reported on the permeation and removal of VOCs from water by various hydrophobic polymer membranes, mainly composed of poly(dimethylsiloxane) (PDMS), [18][19][20][21][22][23][24][25][26][27][28] zeolite-filled PDMS, [29,30] and various other materials. [31][32][33] In this study, for the purpose of removal of VOCs, such as benzene, from water we prepared organic-inorganic hybrid membranes by the sol-gel method using alkyl methacrylate as an organic compound having high affinity for VOCs and TEOS as an inorganic compound.…”
Section: Introductionmentioning
confidence: 99%